Speech Genre of Reminder and Discursive Conditioning of its Features in Virtual Pedagogical Discourse - T. G. Rabenko; E. S. Denisova; A. D. Chardyntseva (Научный диалог, 2023)
The study examines the genre-defining features of the speech genre “reminder” in virtual pedagogical discourse. The relevance of the research is determined by its inclusion in the problems of modern discourse studies (the problem of discursive conditioning of the genre) and virtual pedagogy (the involving of computer technologies as a means and platform for learning in the information-educational environment). Based on T. V. Shmeleva’s genre survey, the genre features of the speech act “reminder” are described, taking into account their determination by communicative-pragmatic conditions in virtual pedagogical communication. It is established that invariant features of the genre include (1) a communicative goal, which is related to the need to activate the addressee’s existing knowledge, and (2) the presence of language markers — syntactic constructions modeled by verbs remind, remember, and don’t forget. The discursive conditioning of the genre is manifested at the level of its dictum content (the sphere of pedagogical communication united by the semantic field “Teaching”), participants in communication (status-oriented roles of communication participants), and those substantial characteristics that are determined by the electronic information carrier (attachment of media files, communication interactivity).